Designing the trajectories of variant teaching of the basics of artificial intelligence in the school course of computer science taking into account the possibilities of project-research and extracurricular activities - Sergey D. Karakozov; Nadezhda N. Samylkina (RUDN Journal of Informatization in Education)
Problem statement . The mandatory study of the basics of artificial intelligence and data analysis in general education course of informatics is a significant innovation that requires adjusting methodological system of teaching informatics at school. The article presents the results of research on the problem of designing trajectories of variant teaching of the basics of artificial intelligence and data analysis in the course of computer science of basic general and secondary general education in accordance with the requirements of the updated FSES of general education on the basis of current methodological approaches, taking into account the possibilities of project-research and extracurricular activities. Methodology. Theoretical methods of research were used: analysis of scientific publications on the subject of artificial intelligence and data analysis, analysis and comparison of materials of foreign educational standards of different levels of education, review of domestic practices of implementation of the results of pedagogical research on the methodology of teaching computer science on the basis of integrative methodological approach. Results. On the basis of the proposed components of the methodology of teaching artificial intelligence basics and data analysis, the possibilities of designing different learning trajectories in accordance with personal requests of participants of educational relations, as well as for the rational use of resources of the information educational environment of the organization in the implementation of basic educational programs of general education are shown. Conclusion. Designing trajectories of variant teaching of the basics of artificial intelligence in the school course of computer science, taking into account the possibilities of project-research and extracurricular activities, allows to optimize needs of students and resources of educational organizations.